p62-Keap1-NRF2-ARE Pathway: A Contentious Player for Selective Targeting of Autophagy, Oxidative Stress and Mitochondrial Dysfunction in Prion Diseases - Shah, Syed Zahid Ali; Zhao, Deming; Hussain, Tariq; Sabir, Naveed; Mangi, Mazhar Hussain; Yang, Lifeng (Frontiers in Molecular Neuroscience, 2018)
Prion diseases, also termed as transmissible spongiform encephalopathies (TSEs), are a group of fatal neurodegenerative disorders affecting humans and animal species. The conversion of a normal cellular protein, PrPC, into an infectious, protease resistant, abnormal pathogenic form PrPSc, is considered as the etiology of these diseases. The PrPSc accumulates in affected individual’s brain, often in the form of extracellular plaques. The molecular mechanisms of neuronal cell death in these diseases are still unclear. Oxidative stress and mitochondrial dysfunction plays a central role in the pathogenesis of several neurodegenerative disorders including prion diseases. Brain is very sensitive to changes in the redox status. It has been demonstrated that PrPC behaves as an antioxidant, while the neurotoxic prion peptide PrPSc increases hydrogen peroxide toxicity in neuronal cultures leading to mitochondrial dysfunction and cell death. The nuclear factor erythroid 2-related factor 2 (NRF2) is an antioxidant response pathway to protect cells from oxidative stress mediated cell death. Reduced glutathione, the major small molecule antioxidant present in all the mammalian cells, and produced by several downstream target genes of NRF2, counterbalances mitochondrial reactive oxygen species (ROS) production. In recent years, it has emerged that ubiquitin-binding protein, p62-mediated induction of autophagy is crucial for NRF2 activation and elimination of mitochondrial dysfunction and oxidative stress. This review will focus on the structure and regulation of NRF2, oxidative stress in prion diseases, mitochondrial dysfunction in prion diseases, activation of NRF2 in prion diseases, activators of NRF2, and finally the activation of p62-Keap1-NRF2-ARE Pathway as therapy in prion diseases to mitigate the disease progression.